1990
DOI: 10.1099/00222615-31-3-185
|View full text |Cite
|
Sign up to set email alerts
|

Differences in susceptibility of inbred and outbred infant mice to enterotoxigenic Escherichia coli of bovine, porcine and human origin

Abstract: Summary. Infant mice from outbred Swiss OF1 and from inbred DBA/2, C57BL/6, BALB/cBy and CBA strains were screened for usefulness in the diarrhoea model with enterotoxigenic Escherichia coli (ETEC) strains of bovine, porcine and human origin. Mouse strains were either weakly susceptible or not susceptible to ETEC strains of porcine or human origin bearing antigen K88, 987P, CFA/I or CFA/II. In contrast, some mouse strains were highly susceptible to bovine and porcine ETEC strains bearing K99 or F41 or both ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…ETEC fimbria is host-specific (27,28,30), and we have also found that neither K99 ϩ nor CFA/I ϩ ETEC is able to infect adult mice (data not shown), presumably, because of the unavailability of host receptors on the murine intestinal epithelium, confirming what has been reported previously (11). Rather, the Salmonella vaccine vector has the ability to target host mucosal inductive sites, e.g., Peyer's patches (52), therefore enabling the vaccine to reach these sites.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…ETEC fimbria is host-specific (27,28,30), and we have also found that neither K99 ϩ nor CFA/I ϩ ETEC is able to infect adult mice (data not shown), presumably, because of the unavailability of host receptors on the murine intestinal epithelium, confirming what has been reported previously (11). Rather, the Salmonella vaccine vector has the ability to target host mucosal inductive sites, e.g., Peyer's patches (52), therefore enabling the vaccine to reach these sites.…”
supporting
confidence: 90%
“…Although a shift in the type of Th cells elicited as a consequence of K99 fimbrial expression, immune IgA and IgG anti-K99 fimbria antibodies were still produced. To assess whether these differences could impact protective immunity, a Duchet-Suchaux neonatal ETEC challenge model was employed (1,10,11). Groups of CD-1 female mice were orally immunized with one of the Salmonella-K99 constructs or with vector (strain H647) only; they were subsequently mated, and pups were allowed to come to parturition.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this phenomenon may be that the mice used in our experiments were genetically heterogenous outbred animals, making some variation in susceptibility to ETEC likely. Studies of infant mice have shown that there is considerable phenotypic variation with respect to susceptibility to ETEC or its toxins among different inbred strains of mice (3,17,18), indicating that host genetic factors may play a significant role in the acquisition of ETEC infections.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from infant mice, a model for K99-positive ETEC infection, indicate that differences in susceptibility depend on the parental murine strain, and suggest that resistance is inherited as a dominant trait (Duchet-Suchaux et al, 1990). In piglets, it has not been possible to get an insight into the transmission of susceptibility/resistance.…”
Section: Discussionmentioning
confidence: 99%